Recurrent preterm birth: data from the study "Birth in Brazil" - Barbara Almeida Soares Dias; Maria do Carmo Leal; Katrini Guidolini Martinelli; Marcos Nakamura-Pereira; Ana Paula Esteves-Pereira; Edson Theodoro dos Santos Neto (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE Describe and estimate the rate of recurrent preterm birth in Brazil according to the type of delivery, weighted by associated factors. METHODS We obtained data from the national hospital-based study "Birth in Brazil", conducted in 2011 and 2012, from interviews with 23,894 women. Initially, we used the chi-square test to verify the differences between newborns according to previous prematurity and type of recurrent prematurity. Sequentially, we applied the propensity score method to balance the groups according to the following covariates: maternal age, socio-economic status, smoking during pregnancy, parity, previous cesarean section, previous stillbirth or neonatal death, chronic hypertension and chronic diabetes. Finally, we performed multiple logistic regression to estimate the recorrence. RESULTS We analyzed 6,701 newborns. The rate of recurrence was 42.0%, considering all women with previous prematurity. Among the recurrent premature births, 62.2% were spontaneous and 37.8% were provider-initiated. After weighting by propensity score, we found that women with prematurity have 3.89 times the chance of having spontaneous recurrent preterm birth (ORaj = 3.89; 95%CI 3.01-5.03) and 3.47 times the chance of having provider-initiated recurrent preterm birth (ORaj = 3.47; 95%CI 2.59-4.66), compared to women who had full-term newborns. CONCLUSIONS Previous prematurity showed to be a strong predictor for its recurrence. Thus, expanding and improving the monitoring and management of pregnant women who had occurrence of prematurity strongly influence the reduction of rates and, consequently, the reduction of infant morbidity and mortality risks in the country.